What is Happening to ‘Traditional’ Forms of Marriage? A Preliminary Account Using the Free-list Method to Evaluate Changes across Age Groups in Lithuania - Bučius, Žygimantas (Vilnius University Open Series, 2025)
In this paper, I will present the results of data collected between April 2021 and January 2022 on how Lithuanians across four age grades (18–29; 30–39; 40–59 and 60+) perceive marriage. The data was collected by using the systematic emic method of free-listing, which is intended to determine the main concepts comprising a particular cultural domain. A cultural domain is any coherent cultural construct about which many members of a culture share a common understanding. Free-listing is a simple data-eliciting method in which you ask a sample (usually around 30 participants is sufficient) to list all the kinds of things (or concepts) you associate with some cultural domain. The domain may be a coherent set of things, such as kinds of healthy foods, contagious diseases, and prestigious jobs, or it can be more abstract, such as whatever you associate with social justice, Russia, or, in this particular case, marriage. Our research group decided to ask a sample of Lithuanians to “list all the things that come to their mind when they think of marriage.” The instructions and questions were presented in the Lithuanian language. Given that researchers have shown that ideas of marriage have changed significantly in the recent times, we thought it would be interesting to conduct free-lists with four different age groups to compare both differences and similarities. While free-listing is only the first phase of a research project, it allows us to elicit terms reflecting the salient features of the concept of marriage and provides an extensive array of terms showing the distribution of ideas related to marriage. This report shows some of these results.